Use the factor theorem to show that (x-1) is a factor of x^3 - 3x^2 -13x + 15

If (x-1) is a factor of x3 - 3x2 -13x + 15 then one of the solutions for x must be x = 1.(This is because, if (x-1) is a factor of this equation then it is true that x-1=0, because this is a point where the curve crosses the x axis and therefore is = to 0. Solving x-1=0 gives x=1)Because we know that if (x-1) is a factor of the curve, the equation must equal 0 when x=1, we can just substitute this in as such:(1)3 - 3(1)2 -13(1) + 15= 1 - 3 - 13 + 15= 16 -16 = 0Therefore we can conclude, using the factor theorem that (x-1) is a factor of x3 - 3x2 -13x + 15

Related Further Mathematics GCSE answers

All answers ▸

Find any stationary points in the function f(x) = 3x^2 + 2x


Let y = (4x^2 + 3)^4. Find dy/dx.


The equation of a curve is y = x^2 - 5x. Work out dy/dx


Use differentiation to show the function f(x)=2x^3–12x^2+25x–11 is an increasing function for all values of x


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo

© MyTutorWeb Ltd 2013–2025

Terms & Conditions|Privacy Policy
Cookie Preferences